The Implementation and Impact of the Laïcité System on the Development of Islamophobia in France - Wulandari, Safitri; Azzahra, Anandita; Rahmadani, Jihan; Ummah, Aniqotul (Ampera: A Research Journal on Politics and Islamic Civilization, 2024)
Secularism is an ideology that seeks to maintain a clear separation between religion and the state. France is a prominent example of a country adhering to this ideology, reinforced by the laïcité policy, which forms the foundation of French secularism. This article employs a qualitative research method, specifically a literature review of various secondary data sources, to critically examine the role of secularism in France and its contribution to the emergence of Islamophobia in public life. The findings indicate that the implementation of the laïcité policy, particularly as a counter-terrorism measure following the September 11, 2001, attacks on the World Trade Center (WTC) in the United States, has fostered an excessive concern over Muslims, who are frequently associated with terrorism. Consequently, Islamophobia has manifested in France through various forms of discrimination, physical and verbal violence, and hate speech, all of which pose significant threats to the security of Muslim communities in the country. Therefore, while secularism is intended to guarantee freedom for individuals to practice their religion without state interference, the situation in France reveals that secularism has, in fact, imposed restrictions on the practice of Islam.